2021
DOI: 10.1177/03331024211038654
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of headache after COVID-19 vaccination in patients with history of headache: A cross-sectional study

Abstract: Background Headache is an adverse event of coronavirus 2019 (COVID-19) vaccination. Whether patients with history of headache suffer more from vaccination-induced headaches is unknown. We aimed to uncover if headache patients develop more headaches after COVID-19 mRNA vaccination than healthy controls. Methods We performed a questionnaire survey for nursing staff in our hospital from April to May 2021. Based on baseline characteristics, we divided the participants into migraine, non-migrainous headache, and he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
51
1
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(58 citation statements)
references
References 12 publications
4
51
1
2
Order By: Relevance
“…Headache is a very common adverse reaction to the COVID-19 mRNA vaccines, particularly for people who are already susceptible to headaches. In a study based on a questionnaire involving 171 participants, the incidence of headaches was found to be 20.5% after the first vaccine, rising to 45.6% after the second shot ( Sekiguchi et al, 2021 ). A case study described a 37-year-old woman suffering from a debilitating migraine attack lasting for 11 days following the second Pfizer/BioNtech mRNA vaccine ( Consoli et al, 2021 ).…”
Section: Guillain Barré Syndrome and Neurologic Injury Syndromesmentioning
confidence: 99%
“…Headache is a very common adverse reaction to the COVID-19 mRNA vaccines, particularly for people who are already susceptible to headaches. In a study based on a questionnaire involving 171 participants, the incidence of headaches was found to be 20.5% after the first vaccine, rising to 45.6% after the second shot ( Sekiguchi et al, 2021 ). A case study described a 37-year-old woman suffering from a debilitating migraine attack lasting for 11 days following the second Pfizer/BioNtech mRNA vaccine ( Consoli et al, 2021 ).…”
Section: Guillain Barré Syndrome and Neurologic Injury Syndromesmentioning
confidence: 99%
“…We are extremely convinced of the usefulness of vaccination and epidemiological data from several studies indicated an excellent efficacy and safety profile for COVID-19 vaccines ( Vitiello et al, 2021 ). However, while the benefits of the COVID-19 vaccines far outweigh the risks, side effects continue to be reported, some of which are common, such as headache ( Sekiguchi et al, 2021 ) and others are much rarer ( Chan et al, 2022 ; Lazaro et al, 2022 ). Complications most frequently reported with Covishield vaccine (Oxford –AstraZeneca) are injection site pain (91.0%), asthenia (74.3%), headache (68.7%), soreness (55.0%) and fever (47.5%) ( Konu et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Patterns similar to COVID-19 can be observed in cases of vaccine-related headache. Headache occurs early after vaccination [89][90][91][92] and is often accompanied by other systemic symptoms (i.e. myalgia and fever [91]).…”
Section: Post-vaccination Headachementioning
confidence: 99%